Lack of Adiponectin Drives Hyperosteoclastogenesis in Lipoatrophic Mice - Madel, Maria-Bernadette; Fu, He; Pierroz, Dominique D.; Schiffrin, Mariano; Winkler, Carine; Wilson, Anne; Pochon, Cécile; Toffoli, Barbara; Taïeb, Mahdia; Jouzeau, Jean-Yves; Gilardi, Federica; Ferrari, Serge; et al. (Frontiers in Cell and Developmental Biology, 2021)
Long bones from mammals host blood cell formation and contain multiple cell types, including adipocytes. Physiological functions of bone marrow adipocytes are poorly documented. Herein, we used adipocyte-deficient PPARγ-whole body null mice to investigate the consequence of total adipocyte deficiency on bone homeostasis in mice. We first highlight the dual bone phenotype of PPARγ null mice: on the one hand the increase bone formation and subsequent trabecularization extending in the long bone diaphysis, due to the well-known impact of PPARγ deficiency on osteoblasts formation and activity; on the other hand, an increased osteoclastogenesis in the cortical bone. We then further explore the cause of this unexpected increased osteoclastogenesis using two independent models of lipoatrophy, which recapitulated this phenotype. This demonstrates that hyperosteoclastogenesis is not intrinsically linked to PPARγ deficiency, but is a consequence of the total lipodystrophy. We further showed that adiponectin, a cytokine produced by adipocytes and mesenchymal stromal cells is a potent inhibitor of osteoclastogenesis in vitro and in vivo. Moreover, pharmacological activation of adiponectin receptors by the synthetic agonist AdipoRon inhibits mature osteoclast activity both in mouse and human cells by blocking podosome formation through AMPK activation. Finally, we demonstrated that AdipoRon treatment blocks bone erosion in vivo in a murine model of inflammatory bone loss, providing potential new approaches to treat osteoporosis.